Can proline dehydrogenase—a key enzyme involved in proline metabolism—be a novel target for cancer therapy? - Xu, Xiangyuan; Zhang, Guangtao; Chen, Yijia; Xu, Weina; Liu, Yujing; Ji, Guang; Xu, Hanchen (Frontiers in Oncology, 2023)
Emerging evidence suggests that proline metabolism is important for regulating the survival and death of different types of cancer cells. Proline dehydrogenase (PRODH), the an enzyme catalyzing proline catabolism, and the degradation products of proline by PRODH, such as ATP and ROS, are known to play critical roles in cancer progression. Notably, the role of PRODH in cancer is still complicated and unclear, and primarily depends on the cancer type and tumor microenvironment. For instance, PRODH induces apoptosis and senescence through ROS signaling in different types of cancers, while as a protumor factor, PRODH promotes malignant phenotypes of certain tumors under stresses such as hypoxia. In order to assess whether PRODH can serve as a novel target for cancer therpyIn this article, we will provide an overview of the biological functions of PRODH and its double-edged role in cancer in this article.